Phonetic Transformation in the Qur’anic Comma: A Study of Surat Al-Takwir (The International Journal of Educational Sciences and Arts, 2024)
Qur'anic separators are one of the most prominent features of the Qur'anic systems, and form part of the structure of the verses that end with it, and it represents the vocal structure in the Qur'anic surahs, and Surat Al-Takweer is characterised by the diversity of its diverses, and then its vocal diversity, which is closely related to the meaning of the verses in which it appears, that is, the intervals have a dual function: the first: artistic represented by generating the musical rhythm in the text of the surah, and the second: moral - rhetorical in terms of its contribution to highlighting and clarifying the meaning, and perhaps the vocal diversity manifests clearly through the vocal transformation in the commas within the surah, and this transformation creates diverse tones, and achieves harmony, coalition and artistic, moral and rhetorical consistency For verses, and in this research we will address the aesthetics of the vocal transformation in the Qur'anic comma in Surat Al-Taweer Al-Tawir Al-Sasoud Al-Saq, and the aesthetics of proportionality that arise from the vocal transformation between the separators, thus showing the importance of the intervals, their role and function in the text of the surah.
Keywords: Vocal Transformation; Quranic Comma; Rhythm; Petising